A nonlinear viscoelastic constitutive model for cyclically loaded solid composite propellant. (1st August 2020) - Tong, Xin; Xu, Jinsheng; Doghri, Issam; El Ghezal, Marieme Imene; Krairi, Anouar; Chen, Xiong
Abstract: In this paper, a novel nonlinear viscoelastic constitutive model is proposed to describe the mechanical behavior of a polymer matrix composite (HTPB propellant). The model is built upon two stress-dependent nonlinear functions within the hereditary integral formulation of viscoelasticity. After implementation into a finite element code, the proposed model is utilized to simulate the stress-strain responses of cyclically loaded HTPB propellant. The results show that the model is capable of capturing the main characteristics of the hysteresis loops during fatigue process and good quantitative agreement is found under circumstances that self-heating effect is not evident. This paper deepens the understanding of the nonlinear behaviors of composite propellant under cyclic loading.